Pentingnya Literasi Keuangan Bagi Siswa Siswi Di SMK PGRI 31 Legok Kabupaten Tangerang - Aldi Samara; Rr Dian Anggraeni; Rina Sulistyowati (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Recently, people have been shocked by the high level of bad credit among Millennials. Based on the findings of the Otoritas Jasa Keuangan (OJK) (Wibowo, 2024), the number of bad loans for more than 90 days in the peer-to-peer (P2P lending) financial technology industry, or what is known as loans for the individual category, has reached IDR 1,73 trillion as of May 2023. The problem is, the Millennial generation or those aged 19-34 years are the biggest "contributors" of bad credit. Various experts say that the Millennial generation is in debt due to the Fear of Missing Out (FOMO) phenomenon, aka following trends to feel like they are not "missing out". Some other experts think that their financial literacy is low.